Elastic fibre organization in the intervertebral discs of the bovine tail. - Yu, J; Winlove, P; Roberts, S; Urban, J (2002)
Elastic fibres have been revealed by both elastin immunostaining and conventional histological orcein-staining in the intervertebral discs of the bovine tail. These fibres are distributed in all regions of the disc but their organization varies from region to region. In the centre of the nucleus, long (> 150 microm) elastic fibres are orientated radially. In the transitional region between nucleus and annulus, the orientation of the elastic fibres changes, producing a criss-cross pattern. In the annulus itself, elastic fibres appear densely distributed in the region between the lamellae and also in 'bridges' across the lamellae, particularly in the adult. Elastic fibres are apparent within the lamellae, orientated parallel to the collagen fibres of each lamella, particularly in the young (12-day-old) discs. In the region between the disc and the cartilaginous endplate, elastic fibres appear to anchor into the plate and terminate there. The results of this study suggest that elastic fibres contribute to the mechanical functioning of the intervertebral disc. The varying organization of the elastic fibres in the different regions of the disc is likely to relate to the different regional loading patterns.